FROM BASICS TO EXPERTISE: LEVERAGING GOOGLE TRANSLATE AND CHATGPT FOR ENGLISH LANGUAGE LEARNING ACROSS ACADEMIC JOURNEYS - Pratiwi, Berlin Insan; Rakhmasari, Dwi Lia (University of Kuningan, 2025)
This study explores the use of language technology and AI tools, specifically Google Translate (GT) and ChatGPT, among first-year and final-year students at a private higher education institution in Kebumen. The study aims to identify differences and similarities in the use of these tools, focusing on how their usage varies based on academic stage and language-related needs. A descriptive qualitative approach was employed, with 121 students participating through fully completed online questionnaires. The study utilizes both closed- and open-ended questions to gather quantitative and qualitative data on AI usage patterns, which were analyzed through descriptive and thematic analysis methods. The results indicate that GT is more frequently used across both groups due to its ease of use, offering quick and direct translations, while ChatGPT is preferred for tasks requiring deeper understanding and more natural, context-sensitive translations. First-year students primarily use AI tools to translate unknown words and assist with basic comprehension of foreign language materials. In contrast, final-year students demonstrate a more diverse usage pattern, employing AI for tasks such as translating academic texts, understanding journal articles, and preparing for foreign language proficiency tests. Furthermore, the academic needs of the two groups differ significantly, with first-year students focusing on writing and grammar tasks, while final-year students rely more heavily on AI for research and advanced academic activities. The study contributes to the understanding of how language technology and AI tools impact academic life and offers insights into how these tools can be integrated into the educational process to meet the varying needs of students at different levels of study.